2010
DOI: 10.3390/molecules15118507
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory and Anti-Influenza Properties of Components from Chaenomeles speciosa

Abstract: The fruit of Chaenomeles speciosa is a traditional Chinese medicine used for the treatment of dyspepsia and various inflammatory diseases. In the present study, we evaluated the potential radical scavenging capacity, and activity against nitrous oxide, inflammatory cytokines production and neuramindase (NA) of its isolates. The results showed that 3,4-dihydroxybenzoic acid (1) displayed higher inhibitory activities on DPPH and NA with IC50 values of 1.02 μg/mL and 1.27 μg/mL respectively, and quercetin (2) als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 22 publications
(18 reference statements)
2
66
0
Order By: Relevance
“…In addition, Faith and co-workers showed that the mRNA for two immediate-early genes, ICP0 and ICP4 was reduced at 3hpi, 2.1-and 3.3-fold, respectively, when Rsv was present at a high concentration (219 M). Interestingly, the concentration of Rsv used in both studies was much higher than those used in most studies to induce neuroprotection (0.1−50 M) (Ménard et al, 2013;Zhang et al, 2010;Bastianetto et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, Faith and co-workers showed that the mRNA for two immediate-early genes, ICP0 and ICP4 was reduced at 3hpi, 2.1-and 3.3-fold, respectively, when Rsv was present at a high concentration (219 M). Interestingly, the concentration of Rsv used in both studies was much higher than those used in most studies to induce neuroprotection (0.1−50 M) (Ménard et al, 2013;Zhang et al, 2010;Bastianetto et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Modern studies have shown that Chaenomeles speciosa has a variety of biological and pharmacological activities such as immunomodulatory, antiinflammatory, antitumor and antioxidant effects (Dai et al, 2003;Xie et al, 2007;Zhang et al, 2010). Evidence has suggested that glycosides, proteins, amino acid derivatives, tannins and other organic acids are the main bioactive components of Chaenomeles speciosa fruits (Chen et al, 2000;Chen and Wei, 2003;Li and He, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…To the best of our knowledge, this is the first study to demonstrate the ability of compounds 7 and 8 to inhibit ND activity. Compound 9 is a known ND inhibitor [9,24], and was used as a positive control. The ND inhibitory activity of compound 8 was slightly lower than that of compound 9 and similar to that of compound 7.…”
Section: Antioxidative Effects and Nd Inhibitory Activities Of Phenolmentioning
confidence: 99%
“…The free radicals damage DNA, RNA, and proteins, leading to different types of tissue injuries [1,10]. Antiviral agents taken together with antioxidants, antiinflammatory agents, or both demonstrate enhanced activity [8,24]. Therefore, compounds that act as antioxidants and ND inhibitors may serve as powerful therapeutics to control influenza virus.…”
Section: Introductionmentioning
confidence: 99%